Chemicals and lemon essential oil effect on Alicyclobacillus acidoterrestris viability - Maldonado, Maria Cristina (Brazilian Society of Microbiology, 2014)
Alicyclobacillus acidoterrestris is considered to be one of the important target microorganisms in the quality control of acidic canned foods. There is an urgent need to develop a suitable method for inhibiting or controlling the germination and outgrowth of A.acidoterrestris in acidic drinks. The aim of this work was to evaluate the chemicals used in the lemon industry (sodium benzoate, potassium sorbate), and lemon essential oil as a natural compound, against a strain of A.acidoterrestris in MEB medium and in lemon juice concentrate. The results pointed out that sodium benzoate (500–1000–2000 ppm) and lemon essential oil (0.08–0.12–0.16%) completely inhibited the germination of A. acidoterrestris spores in MEB medium and LJC for 11 days. Potassium sorbate (600–1200 ppm) was more effective to inhibit the growth of the microbial target in lemon juice than in MEB medium. The effect of sodium benzoate, potassium sorbate and essential oil was sporostatic in MEB and LJC as they did not affect spore viability.